Assessing the Performance of EU Nature Legislation in Protecting Target Bird Species in an Era of Climate Change. Issue 3 (25th August 2015) - Sanderson, Fiona J.; Pople, Robert G.; Ieronymidou, Christina; Burfield, Ian J.; Gregory, Richard D.; Willis, Stephen G.; Howard, Christine; Stephens, Philip A.; Beresford, Alison E.; Donald, Paul F.
Abstract: International legislation forms a cornerstone of conservation, yet its efficacy is rarely quantified. We assess whether species listed on Annex I of the European Union (EU) Birds Directive, for which EU Member States are obliged to implement special conservation measures, differ systematically in their short‐term (2001‐2012) or long‐term (1980‐2012) population trends from those of non‐Annex I species. In both periods, Annex I species had more positive trends than non‐Annex I species, particularly in countries that joined the EU earlier. There were additional signatures of climate change and life history strategy in the trends of species in one or both periods. Within Annex I species, long‐distance migrants fared significantly worse than other species, suggesting that enhanced protection on the breeding grounds alone may be insufficient for these species. We conclude that the EU's conservation legislation has had a demonstrably positive impact on target species, even during a period in which climate change has significantly affected populations.